Power generation using thermoelectric power generator with parabolic solar concentrator / Aneurin Nanggar Nyandang, Baljit Singh Bhathal Singh and Muhammad Fairuz Remeli - Nyandang, Aneurin Nanggar; Bhathal Singh, Baljit Singh; Remeli, Muhammad Fairuz (2021)
Solar Thermoelectric Generator (STEG), a hybridization system of a thermoelectric generator (TEG) with a heat exchanger have been thoroughly explored because of its ability to produce both electricity and heat simultaneously. In this project, a STEG system consists of parabolic solar dish collector and a single TEG was constructed to produce both heat and electricity simultaneously. An absorber plate placed on the focal point of the dish was used to facilitate the heat transfer of the reflected solar radiation to the TEG through the plate. The absorber plate thickness was 1 mm and made up from copper to ensure high heat transfer rate and was well insulated to ensure minimal heat loss. To evaluate the performance of the STEG, Water-Cooled Cooling Method with Water Heat Sink and Air-Cooled Cooling Method (Forced-Convection) with Finned Heat Sink were introduced to cool down the generators. Results showed that Water-Cooled Cooling Method with Water Heat Sink was more effective to cool down the generator and allow a higher electricity being generated than air-cooled cooling method.